Integration of BMv2 and eBPF/XDP for Dynamic Forwarding in 5G Transport Networks - Mercês, Jefferson M. O. das; Galvão, José S. da S.; Gomes, Ruan D.; Sousa, Marcelo P.; Silva, Moacy Pereira da; Lopes, Waslon Terllizzie A. (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF), 2026)
This paper analyzes the impact on end-to-end latency of 5G applications by integrating eBPF/XDP-based observability mechanisms with programmable switches in the transport network. This proposal uses eBPF to monitor the UPF and identify UE traffic encapsulated in GTP-U tunnels. An orchestrator processes events related to end-to-end delay variation per-flow and dynamically updates the tables of the switches, enabling real-time route switching according to network conditions. The results indicate that the proposed dynamic forwarding mechanism significantly reduces latency under degraded conditions, achieving up to 78% improvement depending on the duration of the degradation period.